Finland : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key findings of the Financial System Stability Assessment concerning Finland. It reveals that Finland's banking system remains well capitalized and profitable. Although low interest rates have squeezed net interest income, banks have increased income from trading and insurance and reduced cost-income ratios, helping to maintain profitability. Nonperforming loans have remained low and capitalization ratios are well above requirements, though buffers may be exaggerated by the aggressive use of risk weights. The Net Stable Funding Ratio suggests that vulnerabilities from maturity mismatches are limited in aggregate. Nevertheless, previously identified vulnerabilities remain, and some have increased.